2011
DOI: 10.1093/jb/mvr121
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-induced mesenchymal transition of MS-1 endothelial cells requires Smad-dependent cooperative activation of Rho signals and MRTF-A

Abstract: Endothelial-mesenchymal transition (EndMT) plays important roles in various physiological and pathological processes. While signals mediated by transforming growth factor (TGF)-β have been implicated in EndMT, the molecular mechanisms underlying it remain to be fully elucidated. Here, we examined the effects of TGF-β signals on the EndMT of mouse pancreatic microvascular endothelial cells (MS-1). By addition of TGF-β2, MS-1 cells underwent mesenchymal transition characterized by re-organization of actin stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
117
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 57 publications
7
117
1
Order By: Relevance
“…4C). As reported by others (Mihira et al, 2012;Minami et al, 2012;Sandbo et al, 2011), we also observed an increase in total MKL1 levels compared to control cells (Fig. 4D).…”
Section: Human Cells Express a Second Shorter Mkl1 Isoformsupporting
confidence: 91%
See 1 more Smart Citation
“…4C). As reported by others (Mihira et al, 2012;Minami et al, 2012;Sandbo et al, 2011), we also observed an increase in total MKL1 levels compared to control cells (Fig. 4D).…”
Section: Human Cells Express a Second Shorter Mkl1 Isoformsupporting
confidence: 91%
“…Current models suggest a complex interplay between TGF-b/Smad3 and the Rho-actin-MKL1 signaling pathways during myofibroblast differentiation (Charbonney et al, 2011;Masszi et al, 2010;Small, 2012). Several studies have shown that TGF-b upregulates total MKL1 expression and triggers the nuclear accumulation of MKL1, but not MKL2, in different precursor cells (Gupta et al, 2013;Mihira et al, 2012;Minami et al, 2012;Morita et al, 2007;Sandbo et al, 2011). However, TGF-b-mediated MKL1 translocation occurs in a delayed fashion compared to direct stimulation of the Rho-actin-MKL1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…12 Interestingly, endothelin-1/endothelin receptor type A-mediated glomerular endothelial cell dysfunction is required for podocyte depletion and progression of glomerulosclerosis in several podocyte injury models. 13 Endothelial fenestrations and surface layer are characteristic hallmarks of differentiated capillary endothelial cells. A reduced number of glomerular endothelial fenestrations in patients with type 1 and type 2 diabetes has been documented.…”
mentioning
confidence: 99%
“…Many studies have pointed to the important role of TGF-␤ receptor signaling and downstream targets, such as RhoA, Smad, and Snail transcriptional repressor in EndoMT (11,18). Additionally, interleukin-1␤ (IL-1␤) has been found to also initiate the transition of endothelial cells to mesenchymal cells in corneal endothelial cells (14).…”
mentioning
confidence: 99%